Engineering Trienoic Fatty Acids into Cottonseed Oil Improves Low-Temperature Seed Germination, Plant Photosynthesis and Cotton Fiber Quality. (7th May 2020) - Gao, Lihong; Chen, Wei; Xu, Xiaoyu; Zhang, Jing; Singh, Tanoj K; Liu, Shiming; Zhang, Dongmei; Tian, Lijun; White, Adam; Shrestha, Pushkar; Zhou, Xue-Rong; Llewellyn, Danny; et al.
Abstract: Alpha-linolenic acid (ALA, 18:3Δ 9, 12, 15 ) and γ-linolenic acid (GLA, 18:3Δ 6, 9, 12 ) are important trienoic fatty acids, which are beneficial for human health in their own right, or as precursors for the biosynthesis of long-chain polyunsaturated fatty acids. ALA and GLA in seed oil are synthesized from linoleic acid (LA, 18:2Δ 9, 12 ) by the microsomal ω-3 fatty acid desaturase (FAD3) and Δ6 desaturase (D6D), respectively. Cotton ( Gossypium hirsutum L.) seed oil composition was modified by transforming with an FAD3 gene from Brassica napus and a D6D gene from Echium plantagineum, resulting in approximately 30% ALA and 20% GLA, respectively. The total oil content in transgenic seeds remained unaltered relative to parental seeds. Despite the use of a seed-specific promoter for transgene expression, low levels of GLA and increased levels of ALA were found in non-seed cotton tissues. At low temperature, the germinating cottonseeds containing the linolenic acid isomers elongated faster than the untransformed controls. ALA-producing lines also showed higher photosynthetic rates at cooler temperature and better fiber quality compared to both untransformed controls and GLA-producing lines. The oxidative stability of the novel cottonseed oils was assessed, providing guidance for potential food, pharmaceutical and industrial applications of these oils.